Population-level Outcomes and Cost-Effectiveness of Expanding the Recommendation for Age-based Hepatitis C Testing in the United States. (6th February 2018) - Barocas, Joshua A; Tasillo, Abriana; Eftekhari Yazdi, Golnaz; Wang, Jianing; Vellozzi, Claudia; Hariri, Susan; Isenhour, Cheryl; Randall, Liisa; Ward, John W; Mermin, Jonathan; Salomon, Joshua A; Linas, Benjamin P
Abstract : Routine hepatitis C virus (HCV) testing is recommended for persons born 1945-1965, but HCV incidence has increased among younger adults. We used simulation modeling to demonstrate that routine testing in adults ≥18 increases lifetime identification, cure rates, and is cost-effective. Abstract: Background: The US Centers for Disease Control and Prevention and the U.S. Preventive Services Task Force recommend one-time hepatitis C virus (HCV) testing for persons born 1945–1965 and targeted testing for high-risk persons. This strategy targets HCV testing to a prevalent population at high risk for HCV morbidity and mortality, but does not include younger populations with high incidence. To address this gap and improve access to HCV testing, age-based strategies should be considered. Methods: We used a simulation of HCV to estimate the effectiveness and cost-effectiveness of HCV testing strategies: 1) standard of care (SOC) – recommendation for one-time testing for all persons born 1945–1965, 2) recommendation for one-time testing for adults ≥40 years (≥40 strategy), 3) ≥30 years (≥30 strategy), and 4) ≥18 years (≥18 strategy). All strategies assumed targeted testing of high-risk persons. Inputs were derived from national databases, observational cohorts and clinical trials. Outcomes included quality-adjusted life expectancy, costs, and cost-effectiveness. Results: Expanded age-based testing strategies increased US population lifetime case identification and cure rates. Greatest increases were observed in the ≥18 strategy. Compared to the SOC, this strategy resulted in an estimated 256, 000 additional infected persons identified and 280, 000 additional cures at the lowest cost per QALY gained (ICER = 28, 000/QALY). Conclusions: In addition to risk-based testing, one-time HCV testing of persons 18 and older appears to be cost-effective, leads to improved clinical outcomes and identifies more persons with HCV than the current birth cohort recommendations. These findings could be considered for future recommendation revisions.